2008
DOI: 10.1007/s11999-008-0402-5
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital Complications and Mortality of Unilateral, Bilateral, and Revision TKA: Based on an estimate of 4,159,661 Discharges

Abstract: Patients undergoing bilateral total knee arthroplasty (BTKA) may have higher complication rates and mortality than those undergoing a unilateral procedure (UTKA). To evaluate this hypothesis, we analyzed nationally representative data collected for the National Hospital Discharge Survey on discharges after BTKA, UTKA, and revision TKA (RTKA) between 1990 and 2004. The demographics, comorbidities, in-hospital stay, complications, and mortality of each procedure were compared. An estimate of 4,159,661 discharges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
136
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 58 publications
6
136
2
Order By: Relevance
“…Analyses of risk-adjusted mortality rates should adjust mortality rates only for baseline comorbid diseases, not complications that arise from surgery [15]. The degree to which this issue influenced our results is unclear, although it has been reported that the majority of common diagnoses are comorbidities rather than adverse events [15,30,36]. Fourth, the NHDS enabled only ascertainment of inpatient outcomes, and thus postdischarge complications [24,40,58].…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of risk-adjusted mortality rates should adjust mortality rates only for baseline comorbid diseases, not complications that arise from surgery [15]. The degree to which this issue influenced our results is unclear, although it has been reported that the majority of common diagnoses are comorbidities rather than adverse events [15,30,36]. Fourth, the NHDS enabled only ascertainment of inpatient outcomes, and thus postdischarge complications [24,40,58].…”
Section: Discussionmentioning
confidence: 99%
“…We used ICD-9 codes to select adult (18 years and older) patients who had a THA (procedure code 81.51) for hip osteoarthritis [3,15] (Table 2) and adverse events (Table 3), based on ICD-9 codes.…”
Section: Methodsmentioning
confidence: 99%
“…We entered variables with a minimum 2% prevalence (with the exception of clinically relevant adverse events [ Table 3] with variables with a 1% minimum prevalence) and p values of 0.001 or less [15] for statistical significance based on the large dataset and to correct for multiple comparisons [13] in stepwise backward logistic regressions for mortality and adverse events and a backward linear regression for days of care. We excluded discharge status in the model of mortality since discharge status contains death as a category.…”
Section: Methodsmentioning
confidence: 99%
“…Advocates of simultaneous TKA have cited benefits of a single anesthetic, shorter cumulative hospital stays, patient convenience and satisfaction, and increased cost effectiveness for the healthcare system without increasing perioperative morbidity and mortality and without compromising the clinical outcomes of the operation [8, 9, 11, 12, 17, 18, 24, 27-30, 32, 35]. Opponents of the simultaneous approach cite increased perioperative complications, including pulmonary embolism, major cardiac events, ileus, higher transfusion rates, confusion, and death [1,4,12,15,21,23,27,33,35]. Concern also exists regarding the financial disincentive to the surgeon for performing bilateral simultaneous arthroplasty procedures [2,6,28].…”
Section: Introductionmentioning
confidence: 99%